A short-term evaluation of a hospital no hit zone policy to increase bystander intervention in cases of parent-to-child violence. (November 2018) - Gershoff, Elizabeth T.; Font, Sarah A.; Taylor, Catherine A.; Garza, Ann Budzak; Olson-Dorff, Denyse; Foster, Rebecca H.
Abstract: This study used a pre/post design to evaluate the implementation of a hospital-wide No Hit Zone (NHZ) bystander intervention around parent-to-child hitting. A total of 2326 staff completed the pre-NHZ survey and received training about the NHZ policy; 623 staff completed the post-test survey 10 months later. A group of 225 parents participated in the pre-NHZ survey and a second group of 180 participated in the post-NHZ survey, also 10 months later. Compared to staff in the pre-NHZ group, staff in the post-NHZ group had more negative attitudes about spanking and more positive attitudes about intervention when parents hit children in the hospital. Few differences were found among the parent pre- and post-groups. This study demonstrated that NHZs are a feasible way to inform and train hospital staff in ways to intervene during incidents of parent-to-child hitting to promote a safe and healthy medical environment. Highlights: Medical center staff support the implementation of a No Hit Zone (NHZ). Post-NHZ, staff are more supportive of intervening when parents hit children. Post-NHZ, staff have more knowledge about how to intervene. NHZ was not associated with changes in parents' support for spanking. Parents cited NHZ materials as a reason they became less supportive of spanking.